THE INFLUENCE OF PERSONALITY TRAITS TO INVESTOR OVERCONFIDENCE BIAS - Irena, Florencia; Arifin, Agus Zainul (International Journal of Application on Economics and Business, 2024)
A stock investor tends to be a risk taker because stock investment has quite high risks with the possibility of producing high returns as well. Investors who are risk takers have quite high overconfidence behavior. They tend to be overconfident when predicting investment results. Factors that have an important role in investor overconfidence bias are personality traits. This research aims to verify the influence of personality traits on investor overconfidence bias. The personality traits in this research consist of neuroticism, extraversion, openness, and conscientiousness. This research is based on the Bounded Rationality Theory. The sample used was 497 data. Data is distributed using an online questionnaire. The analysis was tested with Partial Least Squares - Structural Equation Modeling (PLS-SEM). The research results show that neuroticism and conscientiousness have a positive effect on investor overconfidence bias, extraversion has no effect on investor overconfidence bias, and openness has a negative effect on investor overconfidence bias.